Pengaruh Penggunaan Bahasa Indonesia Sebagai Media Komunikasi Bagi Masyarakat Moi, Kota Sorong - Gaspersz, Sherly; Turot, Novela; Peloan, Gloria Deisi; Azzahra, Ayuni; Waisapy, Carlos (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Indonesia is a country that is rich in diversity, starting with ethnicity, nation, culture, and so on. Language is a medium of communication between humans and also, a proof of Indonesia's diversity. The advancement of existing technology facilitates the dissemination of various types of information. In addition, the occurrence of globalization has also caused the use of the Indonesian language to change, this condition is also experienced by the Moi Community in Sorong City. This journal writing was conducted to find out the role and use of the Indonesian language as a communication tool in the daily life of the Moi community. The method used in writing this journal is a descriptive method with a qualitative approach. Data collection was carried out through literature review or literature review. This literature review is carried out by analyzing and reviewing published books, documents, and scientific journals. Based on the literature review conducted, it can be seen that the Indonesian language has three phases of development. In addition, it can be seen that the use of Indonesian as a means of public communication in everyday life is still not optimal. Communication that occurs in the daily life of the Moi people, the city of Sorong mostly uses their local language. In addition, the use of slang is also one of the reasons that the use of Indonesian as a communication tool in people's daily lives is still not optimal.